MODEL PROBLEM BASED INSTRUCTION PADA MATERI BANGUN RUANG SISI DATAR DI SEKOLAH DASAR - toybah toybah (Jurnal Inovasi Sekolah Dasar, 2014)
Abstract: This study was aim at determining the improvement of learning outcomes of the fourth grade students of SD Negeri 43 Palembang through the model of Problem Based Instruction on the material side of the flat geometry. The method used was Classroom Action Research with research subjects were 30 students of class IVA SD Negeri 43 Palembang in the second semester of the 2013/2014 academic year consisting of 17 male students and 13 female students. The success of this research is based on the percentage of completeness observable student learning outcomes derived from the value of the end of each test cycle. The results of this study showed an increase in learning outcomes, it is seen from the average value of the test results of each end of the cycle and completeness of student learning outcomes, the first cycle of the average value of 68.7 and the second cycle of the average score of 83 while the completeness student learning outcomes by 63% the first cycle and second cycle with a completeness of 82%. Based on the results of this study concluded that the application of the model of Problem Based Instruction can increase student learning outcomes in the material geometry on the flat side of SD Negeri 43 Palembang. Therefore, it is advisable for teachers to use the model of Problem Based Instruction as an alternative model of meaningful learning in math.Keywords: learning outcomes , Model Problem Based Instruction Abstrak: Penelitian ini bertujuan untuk mengetahui peningkatan hasil belajar siswa kelas IV SD Negeri 43 Palembang melalui model Problem Based Instruction pada materi bangun ruang sisi datar. Metode penelitian yang digunakan adalah Penelitian Tindakan Kelas (PTK) dengan subjek penelitian berjumalah 30 orang siswa kelas IVA SD Negeri 43 Palembang pada semester genap tahun ajaran 2013/2014 dengan  yang terdiri dari 17 orang siswa laki-laki dan 13 orang siswa perempuan. Keberhasilan penelitian ini diamati berdasarkan presentase ketuntasan hasil belajar siswa yang diperoleh dari nilai ujian setiap akhir siklus. Hasil penelitian ini menunjukkan terjadinya peningkatan hasil belajar, hal ini terlihat dari nilai rata-rata hasil ujian setiap akhir siklus dan ketuntasan hasil belajar siswa, yaitu siklus I nilai rata-ratanya sebesar 68,7 dan siklus II nilai rata-ratanya sebesar 83 sedangkan ketuntasan hasil belajar siswa siklus I sebesar 63% dan siklus II dengan ketuntasan sebesar 82%. Berdasarkan hasil penelitian dapat disimpulkan bahwa penerapan model Problem Based Instruction dapat meningkat hasil belajar siswa pada materi bangun ruang sisi datar di SD Negeri 43 Palembang. Oleh karena itu, disarankan kepada para guru untuk menggunakan model Problem Based Instruction sebagai alternatif model pembelajaran yang bermakna dalam pelajaran matematika.Kata kunci: Hasil belajar, Model Problem Based Instruction